In Vivo and In Vitro Toxicity Evaluation of Hydroethanolic Extract of Kalanchoe brasiliensis (Crassulaceae) Leaves - Aldilane Gonçalves Fonseca; Luzia Leiros Sena Fernandes Ribeiro Dantas; Júlia Morais Fernandes; Silvana Maria Zucolotto; Adley Antoninni Neves Lima; Luiz Alberto Lira Soares; Hugo Alexandre Oliveira Rocha; Telma Maria Araújo Moura Lemos (Journal of Toxicology, 2018)
The species Kalanchoe brasiliensis, known as “Saião,” has anti-inflammatory, antimicrobial, and antihistamine activities. It also has the quercetin and kaempferol flavonoids, which exert their therapeutic activities. With extensive popular use besides the defined therapeutical properties, the study of possible side effects is indispensable. The objective of this study is to evaluate the toxicity in vitro and in vivo from the hydroethanolic extract of the leaves of K. brasiliensis. The action of the extract (concentrations from 0.1 to 1000 uL/100 uL) in normal and tumor cells was evaluated using the MTT method. Acute toxicity and subchronic toxicity were evaluated in mice with doses of 250 to 1000 mg/kg orally, following recognized protocols. The in vitro results indicated cytotoxic activity for 3T3 cell line (normal) and 786-0 (kidney carcinoma), showing the activity to be concentration-dependent, reaching 92.23% cell inhibition. In vivo, the extract showed no significant toxicity; only liver changes related to acute toxicity and some signs of liver damage, combining biochemical and histological data. In general, the extract showed low or no toxicity, introducing itself as safe for use with promising therapeutic potential.